PENGARUH HARGA, KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Toko Pertanian DEERES Temanggung) - Septian Dian Pradana, 0635020705; ., Muhaimin (Students Journal of Economic and Management, 2016)
This reseach examined the influence of price, service quality and location toward purchasing decision. The object of this reseach was the consumers of Deeres agricultural shop in Temanggung. That data were collected using questionaire which was distributed to fourty five respondent. The instrument was proved valid after the validity test and the variables were also proved reliable after being tested using reliability test. The regression test showed that the price variable was negatively significant toward the purcashing decision, while the service quality and location variables showed positive and significant influence toward the purcashing decision, with location variables as most dominant variable.The result of coefficient determination test model showed that this kind of model was less effective, so that the other variable were needed to influence the purcashing decisionÂ  In the other hand, The anova test showed that this model was well built. Key word : Price, Service quality,Location, Purcashing decision